Retrospective analysis of pan-facial fractures at Wits Oral Health Centre - Gumede, Ntokozo Bhekisisa (University of the Witwatersrand, Johannesburg, 2023)
Aim: This study aimed to retrospectively analyse the characteristics and treatment outcome of pan-facial fractures over five years at Wits Oral Health Centre. Materials and methods: We designed and implemented a retrospective study composed of patients with pan-facial fractures treated at Wits Oral Health Centre. All records from January 2015 to December 2019 were analysed. Primary predictor was pan-facial fracture. Aetiology, location, type and distribution of pan-facial fractures were recorded. Perioperative variables included in the study were patient demographics, comorbidities, associated injuries and treatment outcomes. Results: A total of 34 patients (32 M, 2 F) were included in the study. The mean age of patients was 36 years. The most common aetiology was assault (n=17) followed by road traffic accidents (n=12). Traumatic brain injury was the most common associated injury. All 34 patients had involvement of upper and lower midface fractures. 52 mandibular fractures were recorded in 34 patients. Only two of the 34 patients (6%) had complications. Conclusion: Timing and stepwise management of pan-facial fractures in conjunction with neurosurgical team, focused on restoration of function and facial form, is required for optimal results.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Dentistry (in the Maxillofacial & Oral Surgery) to the Faculty of Health Sciences, School of Oral Health Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Pan-facial fractures; Facial fractures; Neurosurgical; UCTD; Retrospective; Wits Oral Health Centre; SDG-3: Good health and well-being